Utilisation of treated straw from newly-developed PadiU PUTRA-1 rice variety as feed supplement for sustainable goat production - Adewale, Ahmed Muideen (2022)
The persistent challenges of meeting the global population's demand for animal protein in the ruminant industry, centred on feed to boost production. To bridge the niche areas for the realisation of food security, the availability of feed that is cheap, noncompetitive, qualitative, and sustainable is required. Agricultural waste, such as rice straw that is illicitly disposed of, causing health impairment and global environmental nuisance through burning could be improved by biological additive and used as ruminant feed. However, biological additives have been reported to improve straw quality through ensiling and possibly animal performance. As a result, the objective of the study refers to the use of enriched straw from a newly developed rice variety as a feed supplement for a sustainable goat production. This thesis comprised of three research chapters. The aim of the first experiment was to examine the efficacy of biological additives on nutrient profiles, ensile quality, in vitro rumen fermentation in different varieties of treated rice straw; ML4, ML10, ML21, ML24, MR219 and PadiU Putra-1 were ensiled with water (Control), enzyme (E) and combination of bacteria and enzyme (BE) in a complete randomise design (CRD) experiment. The rice straw varieties, obtained from the paddy research farm were chopped to about 2-3 cm, treated according to the above treatments to attain 70% moisture content, compressed in a 1 L jar and ensiled for 30 days. Results showed that treatment with the combination of bacteria and enzyme had lower neutral detergent fiber (42.31%) and lower acid detergent fiber (21.08%) for PadiU Putra-1 than other treatments (enzyme and control) and varieties. For the ensiled extract, the lowest pH, NH3, butyric acid and propionic acid were obtained in BE treatment in most of the rice straw varieties. In addition, straw treated with BE had significantly higher lactic acid content, in vitro gas production kinetics, digestibility, and rumen fermentation compared to the enzyme and control. This study revealed that a combination of bacterial and enzyme treatment effectively improved the quality of treated rice straw, with the PadiU Putra-1 variety being the most outstanding. Selection of the appropriate biological treatment and variety of rice straw is important to improve straw quality. However, the treated rice straw needs further evaluation for its in vivo efficacy. The second experiment investigated the effects of PadiU Putra-1 treated rice straw with biological additives on growth performance, nutrient digestibility, rumen fermentation, microbial population, and relative expressions of ruminal MCT1 and growth hormone genes in goats. Twenty-four male crossbred Boer goats were randomly assigned to the following diets: (i) Control (untreated straw); (ii) Enzyme treated straw; and (iii) BE, enzyme plus lactic acid bacteria treated straw. Each diet, in the form of total mixed ration consisted of 50% treated rice straw and 50% concentrate was fed at 3.5% DM body weight of the experimental animals for 14 weeks. The results showed that average daily gain (ADG) of goats was 13% and 26%, respectively, higher in enzyme and BE treatment than the control (P<0.01). Feed efficiency (gain:feed) was also enhanced by 8% and 23% in Enzyme and BE treatment diets relative to control. Goats fed treated straws had higher nutrient digestibility leading to higher digestible nutrient intake (P<0.001). Dietary treatments had no effect on rumen fermentation except propionate concentrations which were higher in the treated rice straw groups leading to lower acetate to propionate ratio (P<0.01). Goats fed treated rice straw had higher cellulolytic bacteria but lower protozoa and methanogens which resulted in lower methane concentration; greater expression of ruminal MCT1 and hepatic GHR, IGF-1 genes (P<0.01) indicating better rumen absorption, growth process and nutrient metabolism. The third research chapter examines the influence of biologically treated rice straw on blood profiles (haematology and biochemistry), non-carcass, carcass characteristics and meat quality in goats. The blood samples from each animal were taken from the jugular vein using vacuum EDTA and serum tube for haematological and biochemical blood profile analysis ascertain the non-detrimental effect of the diet while the meat quality analysis was performed after the slaughtering and the ageing days. The blood profile results indicated dietary treatment had no detrimental effect on the haematological and biochemical profiles, but the days of sampling had significant effect. On the carcass trait, enzyme treatment increased slaughter weight, hot carcass, and cold carcass by 4%, 6%, and 6%, respectively, compared to the control, whereas BE treatment increased the above parameters by 9%, 13%, and 15%, respectively (P<0.05). In addition, the dietary treatment improved the chilling loss and dressing percentages, but had no effect on the non-carcass and primal cuts. Dietary treatment influenced the cooking loss percentage and shear force, whereas other physicochemical meat qualities were unaffected but had a post-mortem ageing effect.